A COMPARATIVE ANALYSIS OF THE ANTIFUNGAL EFFECTS OF YEAST AND BACILLUS SUBTILIS IN THE CONTROL OF BLUE EYE MOLD DISEASE OF MAIZE AND RICE - Nnebechukwu, Ijeoma Adaku; Rwang, Nerat Yusufu; Ikechi-Nwogu, Chinyerum Gloria; Ibrahim, Omeiza Abdullateef (FUDMA Journal of Sciences, 2024)
Blue eye mold disease cause significant post harvest losses of grains in storage. The need to control the plant disease with the use of bio friendly agents is of paramount importance. This research assessed the antifungal effect of Bacillus subtilis and Yeast (Saccharomyces cerevisiae) in the control of blue eye mold disease that affects maize and Rice grains in storage. The diseased grains were gotten from two storage barns which were Bukuru and Katako market storage barns of Jos Metropolis and the ability of these organisms to inhibit the growth of the pathogenic fungi (Aspergillus glaucus) found in Maize and Rice grain. The research work was carried out at African Center for Phyto medicine and Research University of Jos, Plateau State. The pathogenic organism was isolated by culturing it on the SDA Media in an aseptic condition. Several other subcultures were carried out in order to get the pure isolates of the fungi. Organisms which served as biocontrol were gotten from National Veterinary Research Institute Vom (NVRI), these organisms were incubated on the same plate with the pathogenic fungi. For Bacillus subtilis, it was incubated at 25°C while that of the Yeast was incubated at 30°C. Results showed that Bacillus subtilis inhibited at 59.40% while Yeast inhibited at 95.84%in maize grains from Bukuru while Bacillus subtilis inhibited at 64.80% and yeast at 69.70%. For Katako market B. subtilis inhibited at 57.48% while yeast inhibited at 64.84% for maize grains while for Rice grains B. subtilis inhibited at 48.93% and Yeast...